Solution viscosity – molar mass relationships for poly(butylene succinate) and discussion on molar mass analysis - Q. Charlier; E. Girard; F. Freyermouth; M. Vandesteene; N. Jacquel; C. Ladaviere; A. Rousseau; F. Fenouillot (eXPRESS Polymer Letters)
Poly(butylene succinate) (PBS) is currently developing due to its biodegradability and the similarity of its mechanical properties to those of polyolefins. Relationships between the number average molar mass, Mn, and solution viscosity such as [η] and ηred were derived for this aliphatic polyester. Mn values were determined by end-group analysis and size exclusion chromatography (SEC). Mark-Houwink-Sakurada (MHS) parameters were proposed in two solvents and for the different molar masses and viscosity measurement methods. As an example, the MHS equations were respectively, [η] =6.4•10–4•Mn0.67 in chloroform and [η] = 7.1•10–4•Mn0.69 in 50/50 wt% 1,2-dichlorobenzene/phenol at 25°C for molar masses measured by SEC in hexafluoro isopropanol (HFIP) with poly(methyl methacrylate) (PMMA) standards. Empirical relationships were also suggested to derive Mn directly from reduced viscosity, ηred, which is much easier to determine than intrinsic viscosity. With these data, the number average molar mass of PBS can be conveniently estimated from a single viscosity measurement. In addition, it was shown that PBS contains 1–2 wt% of cyclic oligomers produced during esterification and that molar masses determined by taking this fraction into account or not were significantly different, especially for long chains.